Developing Knowledge Organization Schemes for Classifying and Preserving Maritime Heritage Collections - Radhakrishnan, R.; Chandrasekharan, G. (Indian Journal of Information Sources and Services, 2025)
Maritime assemblages such as ship models, navigation instruments, logbooks, and oral testimonies are central to explaining human use of sea environments on a centuries’ timescale. However, cataloging and conserving such variability of typically sensitive materials is dangerous due to incomplete documentation, missing standard vocabularies, and the dispersed nature of contemporary digital archives. This paper aims to build a balanced Knowledge Organization Scheme (KOS) for maritime heritage collections to enhance their accessibility, discoverability, and preservation over the long term. Employing a qualitative research methodology, we conducted case studies of the existing maritime museums and digital libraries, contrasting metadata practices. We interviewed field experts to arrive at a KOS model with controlled vocabularies, hierarchical taxonomies, and semantic relationships. The model was then validated on a representative set of maritime objects to assess its efficacy and usability. The results suggest that a structured, domain-based KOS enhances archival record consistency and interoperability among institutions. Additionally, it facilitates richer contextualization of maritime artifacts to the advantage of scholarly research and public interest.